THE ROLE OF COLLAGEN SUPPLEMENTATION IN KNEE JOINT DISORDERS: A SYSTEMATIC REVIEW OF CLINICAL STUDIES - Bartłomiej Zarębski; Maja Ćwiek; Klaudia Malec; Amin Omidi; Bartosz Krawiec; Jakub Sójka; Maksymilian Szombara; Michał Mokrzyński; Piotr Szyszka; Olaf Jadanowski (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Collagen is essential for maintaining the structure and function of the knee joint, making it a promising option for managing joint-related conditions. This review explores current clinical research on the impact of collagen supplements on knee pain, mobility, and overall joint health in individuals with osteoarthritis, early arthritis, meniscal injuries, and functional joint discomfort.Materials and Methods: A literature search was conducted using PubMed and Google Scholar, focusing on studies from 2016 onward. Keywords included "collagen," "knee joint," "supplementation," and "osteoarthritis" to identify relevant clinical trials and studies.Main Findings: The review indicates that collagen supplementation, particularly types I, II, and III, offers notable benefits for knee joint health. In patients with osteoarthritis and early joint degeneration, undenatured type II collagen and collagen peptides significantly reduced pain, stiffness, and improved mobility, as measured by standardized tools like WOMAC, KOOS, and VAS. Similar improvements were noted in athletes and active individuals experiencing activity-related knee discomfort, with reported reductions in joint pain and decreased reliance on additional treatment. Certain collagen formulations also improved range of motion and flexibility in both healthy subjects and those with minor joint issues. Additionally, recent studies show that collagen can help those with meniscal injuries by reducing pain, boosting leg strength, and enhancing quality of life.Conclusion: Collagen supplements appear to be a safe and effective option for improving knee joint health, particularly in cases of osteoarthritis and functional joint discomfort. While outcomes vary depending on the collagen type and dosage, overall evidence supports their potential in reducing pain and enhancing joint function across a range of populations.